Learning Sejarah Kebudayaan Islam through Google Sites - Madarik, Muhammad; Puadi, Hairul (STAI Miftahul Ula Nganjuk, 2023)
This research aims to address the issue of students shunning SKI (Islamic Cultural History) due to its perceived boring nature and lecture-based teaching. The study suggests that educators should adopt a more student-centered approach, allowing for greater creativity and critical thinking. To facilitate this, the use of Google Sites is proposed as a tool for creating interactive and engaging teaching materials. The method used involves preparing students to access Google Sites and guiding them through its features and functions. The result shows that using Google Sites can make SKI more interesting and effective, and promote greater student engagement and participation. The research concludes by recommending the use of Google Sites as a valuable teaching resource for educators.